Correlation of ECG Changes With Coronary Angiographic Morphology in Patients Presented With Rest Pain - Sharmin, Shahnur; Siddique, Md Abu; Ahmed, Md Khurshed; Haque, KMHS Sirajul (University Heart Journal, 2008)
The study was performed to see the correlation of ECG changes with CAG findings in patients of unstable angina presented with prolonged rest pain. A total 30 cases were taken and was divided into three groups according to their ST segment and T wave changes in ECG. Echocardiogram was done and selective coronary angiogram was performed in all patients within 5 to 15 days of presentation. The study showed that patient with significant ECG change had more extensive coronary artery involvement than the patients with less significant ECG change or normal ECG with better preserved ejection fraction. So ECG changes can give a clue about severity, long-term prognosis and outcome of the disease. (University Heart Journal 2007; 3 : 57-59)